Testing learning as alternative to the blank slate hypothesis in the honey bee, Apis mellifera - Olav Rueppell; Kayla De Jong; Jacob J. Herman; Cleo Randall (PLoS ONE, 2025)
Reliable recognition of nestmates and discrimination against non-nestmates is key to the integrity of social insect colonies. Cuticular hydrocarbon profiles play a key role in this recognition process in many species, including honey bees. Newly emerged worker bees are largely devoid of cuticular hydrocarbons and therefore believed to represent a “blank slate” that is not discriminated against and instead accepted into other colonies regardless of colony origin. However, instead of being unrecognizable, the absence of cuticular hydrocarbons may also represent a recognizable “Gestalt”. Thus, an alternative hypothesis for the universal acceptance of newly emerged workers may be that older workers in every colony learn the absence of cuticular hydrocarbons as a familiar stimulus that belongs to their colony because other such workers are constantly emerging under normal circumstances. Here, we tested this hypothesis by comparing the response to newly emerged workers between bees that matured in colonies with and without newly emerging bees. Contrary to our prediction, we found no significant difference between these two experimental groups in an aggression bioassay towards newly emerged workers. We thus failed to provide empirical evidence against the blank slate hypothesis. However, the groups displayed significant differences in aggression towards foragers from their own respective colonies, indicating that the emergence of new workers in a colony can affect group discriminatory behavior in honey bees. Furthermore, we identified a negative effect of temperature on aggressive behavior toward newly emerged workers.